The clinical effect of different self-performed plaque control modalities on the gingival inflammation among a sample of Malaysian adults - Ramlan , Rohilah; Bazirgan, Muhamad Husain Kassim; Kamil, Wisam Alaa; Hilal Abbood Al-Bayati, Lina (2011)

(untitled)
Objectives: the aim of this study was to investigate the efficacy of different approach of self-performed plaque removal (mechanical Vs chemical) on the periodontal health status among a sample of Malaysian adults. Methods: thirty seven systemically healthy patients, 20-30 years old and with gingivitis, were recruited for the study. They were randomized into three different groups according to the self-performed plaque control practice (group 1, group 2, and group 3). All subjects received supra and subgingival scaling, and detailed oral self-care demonstration according to mode of oral self-care for each group. The periodontal parameters gingival index GI, plaque index PI, and bleeding on propping BOP were evaluated at baseline and after two months. Results: The results showed improvements for all periodontal clinical parameters for subjects in group 2 and 3, and significant reduction of BOP levels for subjects in group 3 with chemical and mechanical plaque control compared to group 1 with manual tooth brushing only. Conclusion: Dental health professionals should emphasize on the improvement of quality of self-performed mechanical plaque removal and use of adjunct chemical plaque control mouthwashes.